2014
DOI: 10.1016/j.cell.2014.10.041
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 Controls IRES-Mediated Translation of Viruses

Abstract: SUMMARY Fighting viral infections is hampered by the scarcity of viral targets and their variability resulting in development of resistance. Viruses depend on cellular molecules for their life cycle, which are attractive alternative targets, provided that they are dispensable for normal cell functions. Using the model organism Drosophila melanogaster, we identify the ribosomal protein RACK1 as a cellular factor required for infection by internal ribosome entry site (IRES)-containing viruses. We further show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(202 citation statements)
references
References 83 publications
8
186
0
1
Order By: Relevance
“…For instance, the loosely bound eIF3j subunit must be removed from its entry channel location prior to stable accommodation of the HCV IRES mRNA start codon within the P site, possibly promoted by recruitment of the eIF2-TC [123]. Additionally, the eIF3d subunit resides on the rear side of the 40S subunit head (in canonical 43S complexes) near ribosomal protein RACK1, which is intriguingly required for IRES-mediated, but not canonical, translation [124]. Rather than a direct physical interaction between the HCV IRES and RACK1, one possibility is that RACK1 makes remote interactions to the IRES mediated by eIF3.…”
Section: (D) the Structural And Functional Basis Of Hcv Ires : Eif3 Imentioning
confidence: 99%
“…For instance, the loosely bound eIF3j subunit must be removed from its entry channel location prior to stable accommodation of the HCV IRES mRNA start codon within the P site, possibly promoted by recruitment of the eIF2-TC [123]. Additionally, the eIF3d subunit resides on the rear side of the 40S subunit head (in canonical 43S complexes) near ribosomal protein RACK1, which is intriguingly required for IRES-mediated, but not canonical, translation [124]. Rather than a direct physical interaction between the HCV IRES and RACK1, one possibility is that RACK1 makes remote interactions to the IRES mediated by eIF3.…”
Section: (D) the Structural And Functional Basis Of Hcv Ires : Eif3 Imentioning
confidence: 99%
“…Previous studies have revealed that insect susceptibility to viral infection is determined by host factors, which either facilitate (6,7) or restrict viral replication (8)(9)(10). In addition, the bacterial flora, particularly endosymbiotic Wolbachia strains, modifies susceptibility to viral infections (11,12).…”
mentioning
confidence: 99%
“…CD81 29 , RACK1 30 , PI4KIIIα [31][32][33] , and ApoE 8,12,17,34 are important cellular factors in HCV entry, IRES-mediated translation, RNA replication, and assembly, respectively. To determine the specific stage of the HCV life cycle that requires CIDEB, a panel of siRNAs targeting these genes was used.…”
Section: Resultsmentioning
confidence: 99%